The Turns to the Left in Argentina and Uruguay: Presidential Campaigns since 2003 - González, Luis E.; Amadeo, Belén (Revista Latinoamericana de Opinión Pública, 2019)
From the beginning of this century Argentina and Uruguay, as many Latin American countries, underwent a turn to the left. These turns to the left may be called “the Kirchner cycle” (or “K cycle”) in Argentina, after presidents Néstor Kirchner and his wife, Cristina Fernández de Kirchner, and the “Frente Amplio cycle” (FA, Broad Front) in Uruguay, for its leading political party. Argentina’s turn to the left ended in the presidential election of 2015 in which the Kirchnerist candidate was defeated; Uruguay’s FA cycle will run at least until the 2019 presidential election. Since Argentina and Uruguay’s turns are part of a simultaneous regional turn to the left, their respective national leaderships were not the absolute creators of each country’s “turn”. What they did was to give national shape to strong regional waves. These processes were conditioned by national circumstances, which in some respects were clearly different in each of them. Despite deep social similarities, Argentina and Uruguay have different political cultures and histories that shape their electoral campaigns. Thus, this paper probes into the similarities and differences between the two “turns” to the left focusing on their victorious presidential campaigns (2003, 2007 and 2011 in Argentina, and 2004, 2009 and 2014 in Uruguay). This analysis leads to (i) an assessment of the relative importance of historical accidents in the two cycles (high in Argentina, low in Uruguay) and of enduring and different political traditions (high in both countries); (ii) an exploration of the differing nature of the two cycles, and finally, (iii) to some implications regarding the broader, regional turn to the left. Do these stories suggest we should expect continuity or new cycles (e.g. to the right) in Latin America? Or should we rather expect the Latin American turn to the left to dissolve into diverging stories? The paper concludes that the most likely scenario is the latter, “diverging stories”.